2008
DOI: 10.1386/jmte.1.2and3.153_1
|View full text |Cite
|
Sign up to set email alerts
|

Delivering student feedback in higher education: the role of podcasting

Abstract: Student numbers across the higher education sector have risen over recent years and the challenge of creating and delivering an effective learning experience grows evermore complex for the educator. It is necessary to provide prompt feedback to students on their current progress and personal areas for development, which is paramount for improving the quality of their future assessed work and also impacts significantly on individual motivation. Podcasting offers a timely and expedient delivery method for a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
3
15
0
1
Order By: Relevance
“…Overall, the results of our study support conclusions reached in other studies with regard to the benefits to students of audio feedback, especially in terms of the personal nature of this approach to feedback, its clarity, and its suitability for conveying detailed responses (Brearley & Cullen, 2012;Cooper, 2008;Ice, Swan, Kupczynski, & Richardson, 2008;Merry & Orsmond, 2008;Rotheram, 2009). Audio feedback was generally popular with our students, as was also noted by Rotheram (2009) andCann (2014), and students reported that they had a fuller learning experience, also shown by Cavanaugh and Song (2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, the results of our study support conclusions reached in other studies with regard to the benefits to students of audio feedback, especially in terms of the personal nature of this approach to feedback, its clarity, and its suitability for conveying detailed responses (Brearley & Cullen, 2012;Cooper, 2008;Ice, Swan, Kupczynski, & Richardson, 2008;Merry & Orsmond, 2008;Rotheram, 2009). Audio feedback was generally popular with our students, as was also noted by Rotheram (2009) andCann (2014), and students reported that they had a fuller learning experience, also shown by Cavanaugh and Song (2014).…”
Section: Discussionsupporting
confidence: 88%
“…Although logistically problematic in the past (particularly for large courses), the use of audio feedback has increased as recording devices have become more ubiquitous and electronic transmission of audio files has become simpler (France & Wheeler, 2007;Middleton, 2011;Rotheram, 2007). Using this feedback on writing assignments, along with or instead of traditional written feedback, can help to both alleviate student disengagement and encourage students to take feedback more seriously (Bauer, 2011;Cann, 2014;Cavanaugh & Song, 2014;Cooper, 2008;Ice, Swan, Diaz, Kupczynski, & Swan-Dagen, 2010;Ice, Curtis, Phillips, & Wells, 2007;Johanson, 1999;Sipple, 2007;Wood, Moskovitz, & Valiga, 2011). Audio feedback has been shown to be useful in encouraging students to grasp nuance and detail in critiques (Bauer, 2011;Cann, 2014;Cavanaugh & Song, 2014;Ice et al, 2007;Sipple, 2007), and to enhance student retention and application of formative feedback (Bauer, 2011;Ice et al, 2007;Merry & Orsmond, 2008;Sipple, 2007); research shows it to be effective (Brearley & Cullen, 2012;Macgregor, Spiers, & Taylor, 2011;Orsmond & Merry, 2011), well-liked (Rotherham, 2007, and well-used, with students being more likely to open an audio file versus picking up written comments (Lunt & Curran, 2009).…”
mentioning
confidence: 99%
“…Many studies have reported on the personal and engaging nature of audio feedback (e.g. Cooper 2008, Ice et al 2008, Merry & Orsmond 2008 and results discussed earlier add further support to this. What is not clear from this study is the relative importance of, or synergy between, these two elements in enhancing engagement with and the impact of the feedback although we strongly suspect that the timing of the feedback is more important.…”
Section: Student Perceptions Of Formative Audio Feedbackmentioning
confidence: 56%
“…Cochrane later on pursued to do a survey on the efficiency of the program in helping students improve their presentation skills and the result showed that students" overall experience with ViP was positive [11]. Recommendations from researchers to improve students" presentation skills through standardized training viewing their presentations, and comprehensive self-assessment were also supported in these studies [2], [12], [20], [21].…”
Section: Implementing a Virtual Presentation Program In Esl Classroomsmentioning
confidence: 98%